THE INFLUENCE OF CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN, NET INTEREST MARGIN, AND OPERATIONAL EFFICIENCY RATIO ON SHARE PRICES WITH RETURN ON ASSETS AS AN INTERVENING VARIABLES IN BANKING COMPANY LISTED ON THE IDX - Hasibuan, Thezar Fiqih Hidayat (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study aims to examine the effect of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Non Performing Loans (NPL), Operational Efficiency Ratio (BOPO) on Return on Assets (ROA). Testing the effect of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Non Performing Loans (NPL), Operational Efficiency Ratio (BOPO), Return on Asset (ROA) on Stock Prices. Test the effect of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Non Performing Loans (NPL), Operational Efficiency Ratio (BOPO) on Stock Prices through Return on Assets (ROA) as an intervening variable . The object of this research is 44 banking companies listed on the Indonesia Stock Exchange from 2014-2018. The sample was selected using purposive sampling method, namely 25 companies. The analysis method used in this research is multiple linear regression analysis and path analysis. The results of this study indicate that the variable Net Interest Margin (NIM), Non Performing Loan (NPL), Operational Efficiency Ratio (BOPO) has a direct influence on the variable Return on Assets (ROA). Meanwhile, the variable Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) do not have a direct effect on the variable Return on Assets (ROA). The variable Net Interest Margin (NIM), Non Performing Loan (NPL), Operational Efficiency Ratio (BOPO), and Return on Asset (ROA) have a direct influence on the variable Stock Price. while the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) variables do not have a direct effect on the Share Price variable. The variable Net Interest Margin (NIM), Operational Efficiency Ratio (BOPO) has an influence on the variable Stock Price through the variable Return on Assets (ROA). Meanwhile, the variable Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL) had no influence on the variable stock price through Return on Assets (ROA).